Comportamento dinâmico da região MLT tropical durante o Ciclo Solar 23 - Araújo, Luciana Rodrigues de (2017)
Wind data obtained between 1999 and 2016 from measuments by meteor radar at Cachoeira Paulista (22.7°S, 45.0°W), Brazil, were used to investigate the behavior of the dynamics on upper mesosphere and lower thermosphere region, the interannual variability in the winds, in the diurnal tide and 2-day wave amplitudes and the possible causes. The results show that zonal wind is characterized by a semiannual variation below 90 km and annual above, while the meridional wind exhibits an annual cycle at all altitudes. Monthly winds did not show quasi-biennial variation (QBO), however the seasonal winds in the zonal direction observed during the summer and fall show QBO variations type in altitudes below 90 km. The results also suggest that the zonal and meridional winds are intensified during the years of solar maximum, especially in the summer and winter seasons. The monthly amplitudes of diurnal tide show an annual variation, in which the amplitudes are greater during the eastward phase of QBO at 30 hPa. The spectrum obtained from the deseasonalized amplitudes shows a 26 months peak in the meridional component, which may to be associated with stratospheric QBO phase. The modulation of the diurnal tide amplitude by QBO shows a quasi ten-year variation, and is stronger for the solar cycle maximum. The amplitude of the 2-day wave exhibit interannual variability, however, do not shows to be affected by the QBO phase during the summer season. The amplitudes of the 2-day show interannual variability, but, only in winter it is affected by the QBO phase. Good agreement between the variation of the amplitude of the 2-day wave for meridional wind and the solar radio flux was observed for most of the summers with a significant correlation, suggesting a possible wave modulation by the 11-year solar cycle.